How do community responses from global south contribute to climate justice and resilience debate? - Seleguim,Fabiana Barbi (2021)
Abstract “Towards a just climate change resilience: Developing resilient, anticipatory and inclusive community response” fills an important gap in literature about climate justice and community responses by focusing its lenses in the global south. Designedly, the chapters cover the issue in all the continents where territories and their populations are located in the global south: Brazil and Uruguay (South America), Bangladesh (Asia), Mozambique (Africa) and Solomon Islands (Oceania). The biggest lesson learned from the cases is that strengthening the role of communities and multi-stakeholder coalitions is essential to reduce the injustices and inequalities inherent in anthropogenic climate change, in the face of deforestation, water contamination, declining catches, political instabilities and other economic impacts.